GEOLOGICAL POSITION AND COMPOSITION OF PICRITES FROM THE NOVOUKRAINKA DYKE FIELD (INGUL MEGABLOCK OF THE UKRAINIAN SHIELD) - Mitrokhin, O.; Vishnevska, E.; Gatsenko, V.; Mihalchenko І. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A study has been conducted into the uncommon dyke rocks with ultrabasic composition which were opened with deep boreholes within the Novoukrainka Granite Massif located in the Ingul megablock of the Ukrainian Shield. The research was aimed at specifying the geological position of the studied dyke rocks, as well as clarifying their petrographic features and the presumptive metallogenic specialization. The results of drilling showed that ultrabasites form small dyke bodies of northwesterly extension intruding in the Novoukrainka complex granitoids of 2040-2000 Ma UPb isotope age. The isotope age of the ultrabasic dykes has not been precisely determined. Together with the more numerous olivine dolerite and diabase dykes, the ultrabasic dykes form the Novoukrainka Dyke Field (NDF) flanking the southwest Novoukrainka granitoid massif on the northwestern border of the Bobrinets dyke belt. Cores from the wells were studied using optical and electronic microscopy, electron probe microanalysis, emission spectral analysis and "wet" chemistry. The results suggest that the NDP ultrabasic dyke rocks can be referred to subalkaline picrites altered to a certain extent by low-temperature post-magmatism. The relic paragenesis of mafic minerals characteristic of subalkaline magmas (Ti-salite and kaersutite) can be associated with primary hyperalkalinity of the picrites. High TiO2 in the studied rocks caused by high concentrations of ilmenite and Ti-magnetite is also primary in origin. Relic microtexture features of the picrites testify to fast crystallization of the Ti-oversaturated ultrabasic melt that took place in hypabyssal or even subvolcanic conditions. Low-temperature post-magmatic changes in the picrites were followed by full replacement of olivine and partial replacement of monoclinic pyroxene due to the development of actinolite, biotite, chlorite, pyrites and iron oxides. It has been shown that subalkaline picrites of the NDP are petrographically and geochemically distinct from other dyke rocks of the Bobrinets belt presented by a low-alkaline dolerite-diabase association belonging to the tholeiitic series. As is evident, subalkaline picrites refer to a different rock association, which requires further research into their geologic age, geotectonic position and petrogenesis, their peculiar Ti-V-Ni metallogenic specialization being of scientific interest as well.